2018
DOI: 10.1186/s40798-018-0157-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity Interventions Comprising Wearables and Smartphone Applications on Physical Activity: a Systematic Review and Meta-analysis

Abstract: BackgroundWorldwide physical activity levels of adults are declining, which is associated with increased chronic disease risk. Wearables and smartphone applications offer new opportunities to change physical activity behaviour. This systematic review summarizes the evidence regarding the effect of wearables and smartphone applications on promoting physical activity.MethodsPubMed, EMBASE and Cochrane databases were searched for RCTs, published since January 2008, on wearables and smartphone applications to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
152
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 226 publications
(169 citation statements)
references
References 57 publications
(226 reference statements)
10
152
4
3
Order By: Relevance
“…Notably, parents are early adopters of wearable activity trackers and the number one motivating reason for using these devices is ‘improving health’ [ 20 ]. Recent systematic reviews [ 21 , 22 , 23 ] have shown that interventions using activity trackers combined with apps can effectively increase physical activity in children and adults. The popularity of activity trackers and apps in the general population and their proven efficacy in both children and adults suggest that this technology has great potential to promote physical activity in families.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, parents are early adopters of wearable activity trackers and the number one motivating reason for using these devices is ‘improving health’ [ 20 ]. Recent systematic reviews [ 21 , 22 , 23 ] have shown that interventions using activity trackers combined with apps can effectively increase physical activity in children and adults. The popularity of activity trackers and apps in the general population and their proven efficacy in both children and adults suggest that this technology has great potential to promote physical activity in families.…”
Section: Introductionmentioning
confidence: 99%
“…For example, wearable devices, such activity and sleep trackers and blood pressure and heart monitors, bring new possibilities in delivering effective and tailored behavioral change interventions to increase the frequency and intensity of physical exercise. Results of a recent meta-analysis showed that behavioral change interventions comprising both wearable devices and mobile applications are effective in promoting physical activity, measured through objective measure and daily step count, in the general population (Gal et al 2018).…”
Section: Ehealth Behavioral Change Interventionsmentioning
confidence: 99%
“…Informal caregivers and the healthcare team are automatically contacted if necessary. As mentioned above, accelerometer, activity and sleep trackers, blood and heart rate sensors, and step counter integrated in many smartphones are useful wearable devices that foster the possibilities of new eHealth preventive efforts to increase behavioral change, especially in terms of increasing physical exercise (Gal et al 2018). Self-monitoring is also an effective way to promote weight management for the prevention of obesity and overweight problems in adult populations (Burke et al 2011;Madigan et al 2015;Zheng et al 2015).…”
Section: Strategies Of Ehealth Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal caregivers and the healthcare team are automatically contacted if necessary. As mentioned above, accelerometer, activity and sleep trackers, blood and heart rate sensors, and step counter integrated in many smartphones are useful wearable devices that foster the possibilities of new eHealth preventive efforts to increase behavioral change, especially in terms of increasing physical exercise (Gal et al 2018). Self-monitoring is also an effective way to promote weight management for the prevention of obesity and overweight problems in adult populations (Burke et al 2011;Madigan et al 2015;Zheng et al 2015).…”
Section: Strategies Of Ehealth Preventionmentioning
confidence: 99%